Peningkatan kemampuan mengurutkan benda/gambar berdasarkan ukuran melalui permainan buka tutup caping berangka pada siswa kelas I sd muhammadiyah 1 ngrambe - Siti Janawati (Prosiding Konferensi Ilmiah Dasar, 2026)
This classroom action research aimed to improve the ability of first-grade students to sequence objects/pictures based on size through the “buka tutup caping berangka” (numbered cone opening-closing) game at SD Muhammadiyah 1 Ngrambe. The study followed the Kemmis and McTaggart model across two cycles, involving 22 students and one classroom teacher as research subjects. Data were collected through observation, interviews, documentation, and tests, then analyzed using qualitative and quantitative techniques. Results showed that the pre-action average score was 67.27 with 31.8% of students reaching the completion criterion. This increased to an average of 75.45 (50% completion) in Cycle I, and further improved to 78.63 for individual assessment (77.3% completion) and 84.8 for group assessment (100% completion) in Cycle II. These findings indicate that the caping berangka game effectively improves students’ size-sequencing ability while fostering active and enjoyable learning.